The elementary/middle school counselor's survival guide - Schmidt, John J., 1946-; Schmidt, John J., 1946- (San Francisco, CA : Jossey-Bass, 2010)
'The third edition of this best-selling book offers school counselors an expanded, practical resource that is packed with hundreds of ready-to-use ideas, strategies, and tools. This Survival Guide helps counselors to plan and implement an effective counseling program tailored to the needs of all elementary and middle school students. Step by step, the book walks readers through every aspect of the school counselor job, including: designing a comprehensive counseling program, communicating with students and fellow staff, facilitating groups, promoting positive school discipline, integrating a guidance curriculum, intervening in times of crisis, and taking personal and professional care of oneself. The third edition has been fully revised and updated to include coverage of all the latest issues facing school counselors, such as: Reaching out to diverse student and parent populations -- Integrating the ASCA (American School Counselor Assoc.) National Model for designing, delivering, and evaluating a school's counseling program -- Utilizing new technology to improve services to students and parents -- Addressing emerging issues like cyber-bullying, students living in poverty, special needs students in inclusive classrooms, and more This comprehensive resource also includes a wealth of reproducible worksheets, letters, checklists, and forms designed to save time and effort for busy school counselors.'--
What, who, and how of your school counseling program -- Developing your role and creating an identity -- Setting sail and staying afloat -- Identifying responsive services -- Integrating a school counseling program with the curriculum -- Reaching out to diverse populations -- Preparing for crisis intervention -- Selecting responsive services to address students' concerns -- Responding to critical concerns -- Belonging and being with the school -- Involving significant others -- Playing according to the rules -- Helping yourself to help others
Rev. ed. of: Survival guide for the elementary/middle school counselor
Includes bibliographical references and index
Keywords: Counseling in elementary education -- United States; Counseling in middle school education -- United States; Student counselors -- United States